THE BOARDING SCHOOL MEMORIZATION (BST) MODEL FOR IMPROVING QURAN MEMORIZATION MASTERY AT MTS NEGERI 1 PURWOREJO - Nur Maulidina Zahrotul Afiyah; Fatkhurrohman; Ali Imron (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study aims to describe the implementation of the Boarding School Tahfidz (BST) Model in improving students’ mastery of Qur’anic memorization at MTs Negeri 1 Purworejo, identify the supporting and inhibiting factors of the program, and analyze the level of students’ Qur’anic memorization mastery. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. The findings revealed that the implementation of BST was carried out through a boarding school education system that incorporated various tahfidz activities, including ziyadah (adding new memorization), muraja’ah (reviewing memorization), sorogan (individual recitation), simak-simakan (peer listening and correction), and tasmi’ (public recitation of memorization). The supporting factors of the program included a conducive boarding school environment, students’ discipline, exemplary guidance from supervisors, and parental support. Meanwhile, the inhibiting factors consisted of differences in students’ memorization abilities, boredom, physical fatigue, and difficulties in maintaining previously memorized verses. The level of students’ memorization mastery was categorized as good, as most students were able to achieve the memorization targets while maintaining fluency, proper tajwid application, and consistency in muraja’ah. The BST program proved effective in improving the quality of Qur’anic memorization while simultaneously fostering students’ religious character and discipline